Bestiality and Gluttony in Theory and Practice in the Comedies of Giovan Battista Della Porta - Kodera, Sergius (Renaissance and Reformation / Renaissance et Réforme, 2015)
Giovan Battista Della Porta (1535–1615), Neapolitan nobleman, scholar/scientist, and writer famed for books on natural magic and physiognomy, expressed quite explicit views on bestiality—that is, on human beings having sex with animals. Della Porta populated his plays with characters who allude to their desire both to have sex with animals and to assume animal shapes in order to satisfy their yearnings; the gulone (the glutton), an archetypal character that was a cultural relic from Roman comedy, is a case in point. According to Della Porta, eating habits are indicative of other habits that can be expressed in a person’s physical appearance; his fascination with monstrous bodies and their concomitant bizarre sexual desires betrays a tendency to understand human beings as akin to animals, and indicates the porosity, as he saw it, of boundaries between these two worlds.